EP1028 Metastatic patterns do not provide additional prognostic information in patients with FIGO stage IV high-grade serous ovarian cancer. (1st November 2019) - Feng, Z; Wen, H; Ju, X; Bi, R; Chen, X; Yang, W; Wu, X
Abstract : Introduction/Background: The aim of our study was to investigate whether metastatic patterns were associated with prognosis in patients with FIGO stage IV high-grade serous ovarian cancer (HGSC). Methodology: We retrospectively investigated FIGO stage IV HGSC patients who underwent primary staging or debulking surgery between April 2005 and June 2013 at our institution. None of these patients received neoadjuvant chemotherapy. Metastatic patterns were defined as pleural effusion (stage IVA), parenchymal metastases (stage IVB), and extra-abdominal lymph node metastases (stage IVB). Clinical characters and metastatic patterns were compared with chi-squared or Fisher's exact tests as appropriate. Overall survival was analyzed using Kaplan-Meier method and Cox proportional hazards model. Results: A total of 83 consecutive stage IV HGSC patients were identified. 42 (50.6%) patients were sub-classified into stage IVA with pleural effusion. Among the rest stage IVB patients, 19 (22.9%) patients had parenchymal metastases and 22 (26.5%) had extra-abdominal lymph node metastases. Five-year overall survival of stage IVA and IVB patients was 39.7% and 39.4%, respectively (p=0.711). Besides, there were no survival differences among three metastatic patterns (p=0.701). Conclusion: Our study demonstrated that neither the sub-classification into FIGO IVA and IVB nor metastatic patterns of FIGO stage IV provided additional prognostic information. Disclosure: Nothing to disclose.